The factors of retention among employees in Kolej Poly-Tech MARA Bangi - Wan Hizam, Wan Hassan (2016)
This study identifies the significant factors for retaining employees namely, job satisfaction, working environment, career advancement and compensation and benefits. This research was conducted due to persistent low job retention reported among employees in Kolej Poly-Tech MARA these days. By quantitative cross sectional survey design and combination of qualitative methods, data were collected from KPTM Bangi on employees using questionnaires as the main data collection instruments and supported by narrative data through interviewing with the respondents. A total of 200 questionnaires were distributed to respondents who had agreed to participate in this study. However, only 155 were returned and usable for further analysis. Data then were analyzed by Statistical Package for Social Sciences (SPSS) using Descriptive Statistics, Reliability Statistics, Correlation Analysis and Multiple Regressions. The result showed that only job satisfaction and compensation and benefits were significantly positively associated with employee retention. Implications of the findings and recommendations for future research are also discussed in this study